Cumulative (dis)advantages and gender in working-class trajectories in Buenos Aires - Seid, Gonzalo (2021)
This article deals with processes of accumulation of advantages and disadvantages in trajectories of social mobility from the working class, taking into account gender. In order to investigate how working-class trajectories in Buenos Aires Metropolitan Area are shaped by gender in terms of accumulation of (dis) advantages, we made biographical interviews to individuals with different social backgrounds within the working class. Families with more stable situations were able to transmit better conditions for spirals of accumulation of advantages to take place. Among them, some men were able to take full advantage of them, while in women the obstacles to taking advantage were more recurrent.